2007
DOI: 10.1152/ajpheart.01124.2006
|View full text |Cite
|
Sign up to set email alerts
|

Chronic intermittent hypoxia impairs baroreflex control of heart rate but enhances heart rate responses to vagal efferent stimulation in anesthetized mice

Abstract: Z. Chronic intermittent hypoxia impairs baroreflex control of heart rate but enhances heart rate responses to vagal efferent stimulation in anesthetized mice. Am J Physiol Heart Circ Physiol 293: H997-H1006, 2007. First published March 23, 2007; doi:10.1152/ajpheart.01124.2006.-Chronic intermittent hypoxia (CIH) leads to increased sympathetic nerve activity and arterial hypertension. In this study, we tested the hypothesis that CIH impairs baroreflex (BR) control of heart rate (HR) in mice, and that decreased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
88
3
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 95 publications
(102 citation statements)
references
References 49 publications
7
88
3
2
Order By: Relevance
“…These rats were anesthetized with an ip injection of sodium pentobarbital (40 mg·kg -1 ). The surgical procedure was in accordance with previous studies [17][18][19] . Briefly, supplemental doses of anesthetics (0.1 mL of 1% sodium pentobarbital) were administered every 30 min to prevent eye blinking and pedalwithdrawal reflexes.…”
Section: Surgical Proceduresmentioning
confidence: 99%
“…These rats were anesthetized with an ip injection of sodium pentobarbital (40 mg·kg -1 ). The surgical procedure was in accordance with previous studies [17][18][19] . Briefly, supplemental doses of anesthetics (0.1 mL of 1% sodium pentobarbital) were administered every 30 min to prevent eye blinking and pedalwithdrawal reflexes.…”
Section: Surgical Proceduresmentioning
confidence: 99%
“…Similarly, animals exposed to intermittent hypoxia show potentiated sympathetic discharges and vascular responses to hypoxia, and develop systemic hypertension (Dick et al, 2007;Fletcher et al, 1992, Greenberg et al, 1999, Zoccal et al, 2008. The autonomic hyperactivity is associated with a reduction of the efficiency of the baroreflex control of heart rate and alterations of heart rate variability in OSA patients (Narkiewicz et al, 1998b, Shiomi et al, 1996 and animals exposed to intermittent hypoxia (Lai et al, 2006;Lin et al, 2007;Rey et al, , 2008. Thus, it is likely that the enhanced sympathetic activity along with the reduction of the baroreflex efficiency would impair the regulation of heart rate and the vasomotor tone of blood vessels eliciting hypertension.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it is likely that the enhanced sympathetic activity along with the reduction of the baroreflex efficiency would impair the regulation of heart rate and the vasomotor tone of blood vessels eliciting hypertension. Besides that, it has been found that intermittent hypoxia produces parasympathetic withdrawal, attributed in part to neuronal loss in the vagal ambiguous nucleus (Lin et al, 2007, Yan et al, 2008.…”
Section: Introductionmentioning
confidence: 99%
“…enhances CB chemosensory discharge in normoxia and in response to hypoxia. 12,19,[23][24][25] Furthermore, it has been shown that arterial blood pressure (BP) rapidly increases after 3 to 4 days after CIH exposure, 14,[26][27][28] which is consistent with the time required to potentiate the neural discharges from the CB chemoreceptor during CIH .19,24 Despite all the advances related to the contribution of CB chemoreception to the cardiovascular consequences of CIH, there are no studies showing the role played by the CB chemoreflex once the hypertensive phenotype has become expressed because of CIH exposure. It is worth noting that it is fundamental from a translational perspective because in previous studies performed by Fletcher et al,20 the CBs were removed before the start of CIH and, therefore, before the development of systemic hypertension.…”
mentioning
confidence: 99%
“…[8][9][10][11][12][13][14] Although the link between OSA and hypertension is well established, the mechanisms responsible for the autonomic imbalance and the hypertension are not entirely known. CIH produces oxidative stress, inflammation, and endothelial dysfunction that contribute to the hypertension.…”
mentioning
confidence: 99%